Predators and Geometric Mosaic at the Bath of the Umayyad Palace at Qastal–Jordan: A Comparative Study - Nassar, Mohammad; Turshan, Nizar; Al-Jbour, Khaled (مركز عبد الرحمن السديري الثقافى, 2021)
يعد الحمام الغربي في قصر القسطل من الفترة الأموية المبكرة واحدا من أهم الأبنية ذات الأرضيات الفسيفسائية الهندسية، وتصوير الحيوانات في الأردن. يهدف هذا البحث لدراسة التصاميم الفنية ومقارنتها مع ما يماثلها، لفهم التأثيرات الفنية من المنطقة وخارجها؛ حيثما أمكن. وقد تم اختيار أمثلة مقارنة من مواقع قريبة نسبيا حتى يمكن الحصول على نظرة شاملة حول إنتاج الفسيفساء في المنطقة. إن مشهد الزخارف الحيوانية المفترسة التي وجدت في موقعين إسلاميين هما، حمام القسطل، وقصر خربة المفجر من الأمثلة الإسلامية القليلة والتي يمكن مقارنتها بأمثلة محلية من المنطقة ومن أماكن خارجية، على الرغم من أن هذا النوع من الفنون نادر في فن الفسيفساء الأموية وخارج عن السياقات العقائدية في البُعد عن تمثيل الكائنات الحية البشرية والحيوانية، ولم تظهر في مبان دينية كالمساجد مثلا؛ ما يدل على آنها اجتهادات شخصية من قبل أصحاب تلك القصور، ولم يعتنوا بمسألة أبعادها الدينية. وقد حاول الباحثون تمييز المصادر الرئيسة للتأثيرات الفنية في القسطل، وبخاصة تلك القادمة من آسيا الصغرى وأماكن أخرى خارجية.
The Western Bath at Qastal, an early Umayyad period is one of the most important structures with geometric mosaic pavements in Jordan. The purpose of this study is to examine the individual designs in comparison with others to understand the influences of the region and beyond. Wherever possible, comparative examples have been chosen from sites that are relatively close so that a comprehensive overview of mosaic production in the region may be made possible. The predators’ motif scene found in the two Islamic sites of the Bath at Qastal, and khirbet Al - Mafjar is among the very few examples from the Islamic periods that can be compared with similar examples in the area and elsewhere. This type of mosaic picturing humans and animals was rare during the Ummayad period due to religious reasons. Therefore, it never appeared in worship places such as mosques. This indicates that this type of mosaic was no more than a personal effort made by the owners of those palaces who might not have thought of their religious dimensions, either. Every effort had been made to discern the major sources of influence at Qastal, and in particular those coming from Asia Minor and elsewhere outside of the region.
Keywords: الأرضيات الفسيفسائية -- الفسيفساء الأموية -- التاريخ الإسلامي -- القيم الفنية